Leading excellence : a report on the Leading excellence - application of the engaging leadership framework (ELF) to new higher education sites and contexts project. - Bennett, Lorraine; Hempsall, Kay (Australian Learning & Teaching Council, 2010)
The 'Leading Excellence - Application of the Engaging Leadership Framework (ELF) to new higher education sites and contexts' project builds on an earlier Leading Excellence project -'Leadership for implementing improvements in the Learning and Teaching Quality Cycle', which informed the development of a leadership tool, the Engaging Leadership Framework (ELF). The ELF is a simple, yet sophisticated model which promotes and supports an holistic approach to leading change. It is based on a trilogy of excellence: excellence in scholarship, excellence in engagement and excellence in management. It incorporates a quality cycle positioned to commence with consideration of evidence, culture and context. Also, the framework advocates that leadership is most effective when it is inclusive, shared and respects those in formal and informal leadership roles. The purpose of the project was to assess the ELF's robustness and potential to support effective leadership of change and improvement across the higher education sector. Four sites were selected to trial the ELF. These sites included a multicampus, dual-sector university in regional Victoria (University of Ballarat), a single-campus regional university in New South Wales (University of New England), a large multi-campus metropolitan university in Western Australia (Edith Cowan University) and an offshore campus in South Africa, owned by Australia's biggest university (Monash South Africa). [p.ix]